Low-cost GNSS receivers for geodetic monitoring purposes - Hamza, Veton (Informatica (Ljubljana), 2023)
This article is an extended abstract of the doctoral dissertation entitled “Cost-effective GNSS receivers for geodetic monitoring” 1. For several years, geodetic Global Navigation Satellite System (GNSS) receivers have been argued as proper sensors to monitor natural hazards and engineering structures. Nevertheless, their use is questionable in areas where there is a risk of instrument damage considering their high costs. Therefore, low-cost GNSS receivers are considered as an alternative for such applications. Through various evaluation tests designed and conducted in the doctoral dissertation, substantial analyses for data and positioning quality, size of detected displacements, and application of low-cost GNSS receivers in geodetic monitoring were obtained. The developed Low-Cost GNSS Monitoring System (LGMS) represents a suitable solution for near real-time continuous geodetic monitoring with high accuracy and reduced costs. Furthermore, it can be applied in the geodetic monitoring of natural hazards like subsidences, sinking phenomena, and landslides, as well as, other engineering structures such as viaducts, bridges, dams, mining areas, and chimneys, provided it meets the accuracy standards.
Keywords: displacement; geodesy; geodezija; GNSS; low-cost GNSS receivers; monitoring; nizkocenovni GNSS sprejemniki; premiki